Humusica - Soil biodiversity and global change - Zanella, Augusto; Ascher-Jenull, Judith; Ponge, Jean-François; Bolzonella, Cristian; Banas, Damien; Nobili, Maria De; Fusaro, Silvia; Giannini, Raffaello (Bulletin of Geography. Physical Geography Series, 2018)
Born in Trento (Italy, 2003) for standardizing vocabulary and units of humus form classification, after publishing a first synthetic classification e-book (Zanella et al., 2011), the Humus group decided to use its classification for facing global change (Zanella and Ascher-Jenull, 2018). The classification was detailed in many scientific articles published in three special issues (Humusica 1, 2 and 3) of the journal Applied Soil Ecology. The main seven ideas that supported the whole Humusica project are briefly presented here: soil covers all planet Earth surfaces (soil as the seat of processes of organic matter storage and recycling); soil is only a biogenic structure (with a debate about the definition of the word “soil”); soil may be involved in the process of natural evolution (through a process of organism’ recycling of biomass after death); agricultural soils correspond to simplified natural soils (comparison between natural and agricultural soils); TerrHum, an appeal for classifying forest humipedons worldwide (a first attempt to use a smart cell phone as a field manual for humus form classification). Organic waste and agricultural soils. Is traditional agriculture economically sustainable? Comparing past traditional (1947) and today intensive farm practices in the Venice province of Italy.